2016
DOI: 10.1371/journal.pone.0146712
|View full text |Cite
|
Sign up to set email alerts
|

Bait Preference of Free-Ranging Feral Swine for Delivery of a Novel Toxicant

Abstract: Invasive feral swine (Sus scrofa) cause extensive damage to agricultural and wildlife resources throughout the United States. Development of sodium nitrite as a new, orally delivered toxicant is underway to provide an additional tool to curtail growth and expansion of feral swine populations. A micro-encapsulation coating around sodium nitrite is used to minimize detection by feral swine and maximize stability for the reactive molecule. To maximize uptake of this toxicant by feral swine, development a bait mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 35 publications
2
68
0
Order By: Relevance
“…This reward, ample supply, and/or timely resupply of the attractant increase the probability of repeat visitation by wild pigs to an attractant site. Previous research demonstrated a black-colored peanut paste performed equally as well as whole-kernel corn for eliciting wild pig visitations though it was noticeably more fragrant (Snow et al 2016b). Further, Campbell et al (2006) concluded that peanut-based attractants elicited more visitations by wild pigs than raccoons (Procyon lotor) or collared peccaries (Pecari tajacu).…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…This reward, ample supply, and/or timely resupply of the attractant increase the probability of repeat visitation by wild pigs to an attractant site. Previous research demonstrated a black-colored peanut paste performed equally as well as whole-kernel corn for eliciting wild pig visitations though it was noticeably more fragrant (Snow et al 2016b). Further, Campbell et al (2006) concluded that peanut-based attractants elicited more visitations by wild pigs than raccoons (Procyon lotor) or collared peccaries (Pecari tajacu).…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%
“…Food attractants targeting smell and taste Recently, there has been a focus on identifying preferred attractants for wild pigs designed for the delivery of pharmaceuticals or toxicants Campbell and Long 2007;Snow et al 2016b). Most attractants attempt to exploit the sense of smell, because it is renowned as the most developed sense of wild pigs.…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%
See 3 more Smart Citations